2012
DOI: 10.2527/jas.2011-4035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded levels of niacin supplementation of a semipurified diet on energy and nitrogen balance, growth performance, diarrhea occurrence, and niacin metabolite excretion by growing swine1

Abstract: Thirty-six crossbred barrows with an average initial age of 42 d and BW of 13.8 kg were placed in individual metabolism crates in a 35-d experiment to evaluate the supplementation of a semipurified diet with graded levels of crystalline niacin. Response criteria were energy and N balance, growth performance, occurrence of niacin deficiency diarrhea, and urinary excretion of the niacin metabolite N(1)-methyl-2-pyridone-5-carboxylamide (PYR). The basal diet met the true ileal Trp requirement of growing swine, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…All data available in the public literature demonstrate that nicotinamide when fed to animals is an efficacious source of niacin (see, for example, Da Silva et al, 1952;Baker et al, 1976;Yen et al, 1978;Copelin et al, 1980;Waldroup et al, 1985;Harms et al, 1988;Real et al, 2002;Ivers and Veum, 2012). Data on requirements, allowances and recommendations for feed supplementation are easily accessible as standard literature for animal nutrition experts.…”
Section: Efficacymentioning
confidence: 99%
“…All data available in the public literature demonstrate that nicotinamide when fed to animals is an efficacious source of niacin (see, for example, Da Silva et al, 1952;Baker et al, 1976;Yen et al, 1978;Copelin et al, 1980;Waldroup et al, 1985;Harms et al, 1988;Real et al, 2002;Ivers and Veum, 2012). Data on requirements, allowances and recommendations for feed supplementation are easily accessible as standard literature for animal nutrition experts.…”
Section: Efficacymentioning
confidence: 99%
“…Growth performance was calculated during the preinoculation period (−13 to 0 DPI), and in 2 postinoculation periods (0 to 5 DPI [acute phase], and 5 to 10 DPI [recovery phase]). Beginning at study initiation, pigs were observed twice daily and subjectively scored for the incidence of diarrhea as previously outlined by Ivers and Veum (2012). Daily observations were conducted by 2 individuals independently, and observers were blinded to dietary treatment.…”
Section: Growth Performance and Frequency Of Diarrhea Analysesmentioning
confidence: 99%
“…Data on requirements, allowances and recommendations for feed supplementation are easily accessible as standard literature for animal nutrition experts. All data available in the public literature demonstrate that nicotininc acid and nicotinamide when fed to animals are efficacious sources of niacin (see, for example, Da Silva et al, 1952;Baker et al, 1976;Yen et al, 1978;Copelin et al, 1980;Waldroup et al, 1985;Harms et al, 1988;Oduho and Baker, 1993;Real et al, 2002;Ivers and Veum, 2012).…”
Section: Efficacymentioning
confidence: 99%